Convergence analysis and tuning of a sliding-mode ripple-correlation MPPT - Costabeber, Alessando; Carraro, M.; Zigliotto, M. (IEEE, 2014)
The development of fast Maximum Power Point Tracking (MPPT) algorithms for photovoltaic (PV) systems with high bandwidth and predictable response to irradiation transients is attractive for mobile applications and installations under fast changing weather conditions. This paper proposes the convergence analysis of a sliding-mode version of the MPPT based on ripple correlation control (RCC). The contribution of the paper is a dynamic model, useful to derive a set of design guidelines to tune the sliding-mode RCC-MPPT and achieve a desired dynamic performance under irradiation transients, without a dedicated commissioning phase. The research is based on sliding control theory and it includes both the chattering phenomena analysis and a discussion on the effects of reactive parasitic elements in the PV module. The proposed analysis and design have been validated by Matlab simulations first and then with experimental tests on a 35 W panel with a boost converter charging a 24 V battery. The results support the effectiveness of the proposed modelling procedure and design guidelines, showing good agreement between the model prediction and the experimental transient response.